Utilization of Natural Adsorbents (Rice Husk, Charcoal) in Drinking Water Treatment to Reduce Heavy Metal and Microorganism Content - Lieza Corsita (CV. Get Press Indonesia, 2025)
Access to clean drinking water is a fundamental human right, yet millions face contamination from heavy metals and pathogens. This study evaluated the efficacy of natural adsorbents raw rice husk (RH), rice husk ash (RHA), and activated carbon (AC) for treating contaminated water. The adsorbents were prepared, characterized, and tested in batch experiments. Characterization via SEM, FTIR, and BET revealed that activation significantly enhanced properties; AC exhibited the highest surface area (732.5 m²/g) and porosity, followed by RHA and RH. Under optimized conditions (pH 6-7, dosage 2 g/L, contact time 60 min), AC demonstrated superior removal efficiencies for Pb²⁺ (92.6%), As³⁺ (88.4%), and F⁻ (75.1%). Adsorption data best fit the Langmuir isotherm and pseudo-second-order kinetic model, indicating monolayer chemisorption. However, microbial removal was limited (<30% for E. coli), underscoring the need for complementary disinfection. Regeneration studies showed AC maintained >80% efficiency after three cycles. The findings confirm that activated carbon is highly effective, while rice husk ash is a viable low-cost alternative for heavy metal and fluoride removal. For comprehensive water safety, integrating these adsorbents into hybrid treatment systems is recommended.